Language And Culture in Learning Arabic from A Psycho Sociolinguistic Perspective - Hanan Riswar; Agung Setiyawan; Nur Maidah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Humans are naturally driven to express emotions, views, and aspirations through language as the primary tool of communication. Language not only reflects the identity of a community but also serves as a means of conveying cultural values, building identity, and engaging in social interaction. From a psycho-sociolinguistic perspective, language and culture are closely intertwined and mutually influence each other. Culture affects how individuals process information and think, while language serves as a reflection of a society’s norms, traditions, and communication patterns. Arabic language learning, particularly in Indonesia, often focuses on grammatical aspects (nahwu and sharaf), while cultural aspects are frequently neglected. However, understanding the cultural context is essential for enhancing students' communicative competence. The psycho-sociolinguistic approach offers an integration of language and culture in Arabic language learning to make it more relevant to real-life situations. By using authentic texts, simulations, and integrating Arab cultural values, students not only master linguistic aspects but also comprehend the social and cultural contexts behind them.This study employs a library research method by analyzing various scholarly sources. The research findings indicate that integrating culture into Arabic language learning improves contextual understanding, develops communicative competence, and motivates students to learn Arabic holistically. Implementation strategies include using culture-based materials and interactive simulations, while the main challenge regarding teacher’s limited cultural mastery can be addressed through training and providing relevant learning resources. The psycho-sociolinguistic approach offers profound insights into the relationship between language, culture, and society, emphasizing the importance of understanding Arabic not only as a linguistic science but also as a means of cross-cultural communication.